A general strategy for batch development of high-performance and cost-effective sodium layered cathodes. (November 2021) - Xiao, Biwei; Liu, Xiang; Song, Miao; Yang, Xin; Omenya, Fredrick; Feng, Shuo; Sprenkle, Vincent; Amine, Khalil; Xu, Guiliang; Li, Xiaolin; Reed, David
Abstract: High-performance and low-cost transition metal (TM) layered oxides using earth abundant elements are promising cathodes for Na-ion batteries. However, it is challenging to obtain desired materials because the large Na size, different Na occupations and various layer stacking sequences multiply the complication in determining the structure of a given composition and exacerbate uncertainty to the structure-property correlation. In this work, we use the attainment of desired Nax Mny Niz TM1−y-z O2 -based cathode materials as an example to demonstrate a general roadmap for batch development of sodium layered cathodes towards practical applications. A synthesis phase diagram of Nax Mny Ni1−y O2 was created for pre-screening and rational selection of the platform material of P2/O3-structured Na0.85 Mn0.6 Ni0.4 O2 . Cationic potential was leveraged in elemental substitution to further promote the material structural stability and electrochemical performance. Several cost-effective O3 and P2/O3 hybrid cathode materials have been obtained, all of which demonstrate excellent performance. In particular, the Na0.85 Mn0.5 Ni0.4 Ti0.1 O2 delivers a high specific capacity of 130 mAh/g between 2 and 4 V and 91% retention after 500 cycles. The work discovers multiple materials as high-performance and cost-effective Na-ion battery cathodes and offers critical guidance to the rational design of future layered cathode materials. Graphical Abstract: ga1 Highlights: Phase diagram of Nax Mny Ni1−y O2 has been constructed. Na0.85 Mn0.6 Ni0.4 O2 can be used as platform composition for desired O3 and P2/O3 hybrid structures through Mn substitution. Batch synthesis of materials with excellent sodium-ion battery performance and reduced cost.